2006
DOI: 10.1093/chemse/bjl034
|View full text |Cite
|
Sign up to set email alerts
|

Taste-Signaling Proteins Are Coexpressed in Solitary Intestinal Epithelial Cells

Abstract: The taste system, made up of taste receptor cells clustered in taste buds at the surface of the tongue and the soft palate, plays a key role in the decision to ingest or reject food and thereby is essential in protecting organisms against harmful toxins and in selecting the most appropriate nutrients. To determine if a similar chemosensory system exists in the gastrointestinal tract, we used immunohistochemistry and real-time polymerase chain reaction (PCR) to investigate which taste-signaling molecules are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
292
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(305 citation statements)
references
References 27 publications
13
292
0
Order By: Relevance
“…This is supported by the reduction of the effect of Ile on the induction of HBD2 when cells were treated with an inhibitor of the Gi subunit, Pertussis toxin. mGluR, GPR35 and the extracellular Ca the intracellular calcium ion concentration and activate the ERK signaling pathway, might therefore be candidates for sensing Ile [17][18][19]34]. Further analysis with knockout models for such GPCRs is needed to determine the specific GPCR responsible for the effects of Ile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the reduction of the effect of Ile on the induction of HBD2 when cells were treated with an inhibitor of the Gi subunit, Pertussis toxin. mGluR, GPR35 and the extracellular Ca the intracellular calcium ion concentration and activate the ERK signaling pathway, might therefore be candidates for sensing Ile [17][18][19]34]. Further analysis with knockout models for such GPCRs is needed to determine the specific GPCR responsible for the effects of Ile.…”
Section: Discussionmentioning
confidence: 99%
“…For example, glutamic acid is absorbed into the epithelia, and is also bound to a taste receptor which is one of the GPCRs. Many types of GPCRs, such as taste receptor and GPR35, are expressed in the intestinal epithelia [18][19][20]. In addi- tion, the functions of some GPCRs are associated with the expression of anti-microbial peptides in neutrophils and gingival cells [21,22].…”
Section: Gpcr Mediates the Effects Of Ile On The Enhancement Of Il-1αmentioning
confidence: 99%
“…It is proposed that nutrient sensing in the GI tract resembles taste signalling on the tongue (Rozengurt and Sternini, 2007;Sternini et al, 2008). Indeed, together with other taste signalling molecules, TRPM5 is expressed in epithelial cells of the gut (Bezencon et al, 2007;Jang et al, 2007;Young et al, 2009), and similar to their function in lingual taste cells, the GI taste signalling elements also respond to tastants in the gut lumen (Jang et al, 2007;Margolskee et al, 2007). TRPM5 is shown to be present in human duodenal L cells, where its expression is inversely related to the blood glucose concentration at least in subjects with type 2 diabetes (Jang et al, 2007;Young et al, 2009).…”
Section: Trpm Channelsmentioning
confidence: 99%
“…TRPM5 is shown to be present in human duodenal L cells, where its expression is inversely related to the blood glucose concentration at least in subjects with type 2 diabetes (Jang et al, 2007;Young et al, 2009). However, important species differences do exist as in the murine gut TRPM5 is not colocalized with any of the classical markers for EEC cells such as chromogranin A, 5-HT, glucagon-like peptide 1, ghrelin and cholecystokinin (Bezencon et al, 2007;Kokrashvili et al, 2009). In mouse, TRPM5 is mostly expressed in brush cells (Kaske et al, 2007;Bezencon et al, 2008), also referred to as tufted or caveolated cells (Sbarbati and Osculati, 2005a,b;Morroni et al, 2007).…”
Section: Trpm Channelsmentioning
confidence: 99%
“…A 1996 PNAS article by Höfer et al (7) showing that ␣-gustducin, the taste signaling protein first identified in Margolskee's laboratory (8), is localized in gut epithelial cells added considerable weight to this idea. More recently, several investigators reported the expression of bitter, sweet, and umami (savory) taste receptors in the gut (9)(10)(11). The next important step in this discovery process is to determine the function of these gut taste receptors in digestive and ingestive processing.…”
mentioning
confidence: 99%